أهمية تطبيق معيار الإبلاغ المالي Ifrs7 الأدوات المالية: الإفصاحات في إدارة مخاطر شركات التأمين - سعيداني, محمد السعيد; ميلودي, مصطفى (جامعة الوادي - University of Eloued, 2021)
This study aims to determine the impact of risk disclosure in accordance with the international financial reporting standard IFRS 7 on the policy of insurance companies in the management of these risks, through a field study on a sample of accountants in insurance companies in Algeria. We concluded that the descriptive and quantitative disclosure of risks as approved by IFRS 7 contributes to the implementation of an effective risk management policy in insurance companies which would have an impact on their financial position and their business results
The importance of the application of thefinancial reportingstandard IFRS 7 "Financial Instruments:Disclosures" in the risk management of insurance companies -a field study on a sample of Algerian insurance companies
مقال
Keywords: شركات تأمين، مخاطر، إفصاح، إدارة مخاطر.